Polyoxomolybdates and polyoxomolybdovanadates : from structure to functions : recent results - Cindrić, Marina, kemičarka (Array, 2009)
Summary: The authors' review compiles the literature in the field of polyoxomolybdates, POMo, and polyoxomolybdovanadates, POMoV, over the past two decades. The main achievements in the field of synthesis, crystal and molecular structure determinations and applications are presented. The first section describes polyoxomolybdates; their structure starting with a smaller number of building units to the formation of new structural shapes of polyoxomolybdate clusters of supramolecular arhitecture. Polyoxo-molybdates include the compounds with various organic ligands, functionalized polyoxomolybdates and a number of organo-inorganic clusters. Recent synthetic methods such as functionalization and hydrothermal/solvothermal synthesis with a possibility to control the size and shape of the resulting structure are reviewed. The design and synthesis of inorganic-organic hybrid compounds in which POMo anions are combined with organic molecular cations appears as the most successful approach for preparing novel types of molecular based materials with functional properties. The second section covers the polyoxo-molybdovanadate compounds from structure to synthesis. Interesting compounds with the molybdenum- rich region or vanadium rich-region, mixed vanadium-molybdenum polyoxoanions with various oxidation states of the metal atoms and the organic-inorganic hybrid materials are described. The last section reviews the application of the before mentioned compounds. Due to the functionalization of the complexes potential utility in biology and medicine, catalysis and material science is significantly increased. Finally, the importance of large polyoxometalate clusters as target nanosized molecular materials, which present a challenge for the future complex chemistry, is discussed